Development of Character-Value-Oriented Teaching Materials in the Learning Media Course of The Islamic Religious Education Study Program - Rohani, Rohani; Nasution, Wahyuddin Nur; Ananda, Rusydi (Al Irsyad: Jurnal Studi Islam, 2026)
This study addresses the lack of integration of character values in teaching materials for the Learning Media course in Islamic Religious Education, the limited availability of character-based resources, and the less-than-optimal holistic learning experience for prospective educators. The purpose of the research is to develop teaching materials based on character values for this course. The study applies a Research and Development (R&D) approach using the ADDIE model, involving third-semester students of Islamic Religious Education at Universitas Islam Negeri Sumatera Utara. Data collection techniques include expert validation, observation, and statistical analysis using a t-test and N-Gain. The results indicate that the developed teaching materials are effective. The t-test analysis yields a t-value of 6.01, which exceeds the t-table value of 1.69 at the 0.05 significance level, indicating that the null hypothesis is rejected and the alternative hypothesis is accepted. This confirms a significant difference in student learning outcomes before and after using the developed materials. Furthermore, the N-Gain score of 0.88 is categorized as high, indicating a strong improvement in learning achievement. Student learning activities featured active participation, task completion, and group discussions, while lecturers primarily served as facilitators and explainers of material. In conclusion, the development of character-based teaching materials significantly improves student learning outcomes and is effective. This research is significant for enhancing educational quality, strengthening student character, and providing an innovative teaching material model that can be adapted to other higher education courses in a sustainable manner.